2014
DOI: 10.1007/s11255-014-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of mizoribine therapy in elderly patients with membranous nephropathy: comparison with patients not receiving mizoribine

Abstract: Elderly patients with MN who respond poorly to PSL treatment may be treated successfully with MZR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Moreover, no marked liver dysfunction was recorded. Thus, in agreement with other studies [ 4 7 ], our results indicate that MZR is a safe immunosuppressant for long-term use.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, no marked liver dysfunction was recorded. Thus, in agreement with other studies [ 4 7 ], our results indicate that MZR is a safe immunosuppressant for long-term use.…”
Section: Discussionsupporting
confidence: 93%
“…However, CyA also has serious adverse effects such as nephrotoxicity and hypertension, and is not suitable for long-term therapy. From this viewpoint, MZR is known not to have serious adverse events and to be beneficial when administered over a long period [ 4 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that because MZR has a selective inhibitory effect on proliferation of lymphocytes, the rate of side effects is lower than that of other immunosuppressive drugs [ 32 ]. Because MZR in this study was combined, the methylprednisolone pulse was conducted only once, and the total dose of steroids could be reduced considerably without diminishing the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…MZR is widely used in Japan for the treatment of rheumatoid arthritis [ 18 20 ], systemic lupus erythematosus [ 21 , 22 ], nephrotic syndrome (NS) [ 23 , 24 ] and IgA nephropathy [ 25 ] as well as after renal transplantation [ 26 ], and is noted for its low incidence of side effects. In addition, several recent studies have shown that a combination of steroids and MZR is effective in patients with membranous nephropathy (MN) [ 27 29 ]. In this report, we describe the case of an elderly patient diagnosed with FS during MZR monotherapy prior to the addition of prednisolone for the treatment of MN.…”
Section: Introductionmentioning
confidence: 99%